2014
DOI: 10.3109/13816810.2014.926375
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of Keratoconus Susceptibility Sequence Variants inVSX1, TGFBI, DOCK9, STK24, andIPO5Genes in Polish Patients and NovelTGFBIVariant Identification

Abstract: Our investigation showed that KTCN-related sequence variants of analyzed genes were found in a very small proportion of the studied patients indicating that genes other than VSX1, TGFBI, DOCK9, IPO5, and STK24 are involved in the development and progression of KTCN in Polish patients. Our results support the hypothesis about the genetic heterogeneity of KTCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
2
16
0
6
Order By: Relevance
“…[5][6][7] Also, numerous sequence variants in our KTCN research were identified. [8][9][10][11][12] However, because variations in these genes were specific to particular families or populations only, they could not be recognized as causative for KTCN in the general population. The one possible explanation for the absence of genetic KTCN marker(s) is that the studied genes constitute only a minor fraction of the total genetic load and the number of genes altered in KTCN may be higher.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Also, numerous sequence variants in our KTCN research were identified. [8][9][10][11][12] However, because variations in these genes were specific to particular families or populations only, they could not be recognized as causative for KTCN in the general population. The one possible explanation for the absence of genetic KTCN marker(s) is that the studied genes constitute only a minor fraction of the total genetic load and the number of genes altered in KTCN may be higher.…”
Section: Introductionmentioning
confidence: 99%
“…A etiologia do ceratocone envolve múltiplos fatores e o componente genético na sua origem foi confirmado em diversos estudos (13,16,20) . Entre os genes descritos que influenciam a manifestação do ceratocone, o VSX1 e o TGFBI mostraram o maior potencial para o desenvolvimento da doença em pacientes predispostos (16) . Adicionalmente, o gene DOCK9 foi associado ao desenvolvimento do ceratocone (17) .…”
Section: Discussionunclassified
“…Esta mudança de aminoácidos altera a forma e a função da proteína produzida, e está relacionada com desenvolvimento do fenótipo do ceratocone (20) . Outro estudo, realizado in vitro, observou mutações neste mesmo SNP, rs191047852, em que ocorreu uma mutação sinônima (sem a troca de aminoácidos) afetando a tradução da proteína e assim, teoricamente, promovendo o desenvolvimento do ceratocone (16) . Uma outra mutação do tipo polimorfismo de nucleotídeo único no gene DOCK9 foi observada no estudo de CZUGALA et al (2012), relacionada também com o desenvolvimento do ceratocone em uma família equatoriana, no SNP rs7995432 (c.720+43A>G).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Хотя механизм, посредством которого эта мутация приводит к развитию кера-токонуса, не ясен, известно, что мутация располо-жена в домене, который связывает фосфолипиды и может повлиять на соединение белка с клеточ-ной мембраной. Кроме того, локус 13q32 содержит гены IPO5 (importin 5, белок ядерного транспорта) и STK24 (serine/threonine kinase 24), точная роль которых в патогенезе кератоконуса не извест-на, однако мутации этих генов (2380-134A > C и 1089 + 29G > C соответственно) описаны у па-циентов со спорадическим и семейным кератоко-нусом [1,14].…”
Section: генетика кератоконусаunclassified